PENDAMPINGAN PEMBUATAN LAPORAN KEUANGAN BAGI YAYASAN PANTI ASUHAN LENTERA HATI (JANKA : Jurnal PengabdiAN Kepada MasyaraKAt, 2024)
The purpose of this activity is to improve good financial reporting and in accordance with the standards used for the Lentera Hati Orphanage Foundation. The background of the problem is that in recording the finances of the Lentera Hati Orphanage Foundation, it is still simple, namely only recording incoming receipts from donors and expenses for its daily operations. Therefore, through this community service activity, it will provide socialization and assistance in the preparation of financial statements based on ISAK 35 and PSAK on financial reporting of non-profit entities. This activity is carried out through socialization and education, questions and answers, and assistance in the preparation of financial statements. The result of this service activity is that the Foundation has prepared financial statements for the 1st quarter of 2024 based on PSAK 45 including comprehensive income statements, reports on changes in net assets, financial position statements, cash flow statements and notes on financial statements.  The impact of the program that has been implemented shows that this service is that the Foundation is able to prepare better financial reports and according to standards so that it can communicate to external parties related to organizational activities